Vertical Water Silo Design and Analysis - ÖZHAN DOĞAN, Serap; ANIK, Burak Galip; GÖKTAŞ, Umut (International Journal of Computational and Experimental Science and Engineering, 2023)
This study covers the design of the 155 m3 water tank, which is intended to be established in Tersan Shipyard and to be used for the treatment plant, to meet the needs, and the analysis and verification of the design. First of all, the needs were determined and then the solution steps to meet these determinations were determined. The three-dimensional design of the tank, whose material, dimensions and shape were determined, was carried out. In addition, the places where this tank will be fixed were selected and the analysis was carried out in this part by applying the necessary forces to the structure. It was designed using Rhinoceros, a design program, and then Autodesk Nastran finite element analysis program was used. In order for our water tank design to be considered safe, the result of the analysis should be below the maximum Von Mises Stress value occurring in the structure, below 241.68 MPa. Afterwards, the Nastran simulation module was run and as a result of the simulation, Von Mises Stress values of maximum 46.71 MPa and displacement values of maximum 2.136 mm were reached. According to the results obtained, it has been determined that the designed structure is safe